Translating Stefan Heym’s The Architects: A case study of exophonic creative writing and self-translation - (:unkn) unknown (My University, 2020)
Translingualism, Alloglossia, Exophony: different terms with a common denotation. Wright defines exophony as ‘the phenomenon where a writer adopts a literary language other than his or her mother tongue’ (Yoko Tawada's Portrait of a Tongue 2). Wright goes on to distinguish exophonic writers from bilingual writers, by stating that exophonic writers do not achieve the same type of fluency as bilinguals do, as they typically acquire the second language as adults (2). The purpose of this study is to identify segments of the source text (ST) where this lack of fluency becomes apparent. Self-translation, a practice that generally encompasses exophonic writing, is defined by Popovic as “the translation of an original work into another language by the author himself” (19). The second aim of this study is to assess how self-translations can be a helpful resource when translating the ST into another target language (TL).
Keywords: αλλογλωσσία, αυτομετάφραση; exophony, sellf-translation